2016
DOI: 10.1177/1535370216636719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silibinin and vitamin E on the ASK1-p38 MAPK pathway in D-galactosamine/lipopolysaccharide induced hepatotoxicity

Abstract: Apoptosis signal-regulating kinase 1 (ASK1), a redox-sensor mitogen-activated protein kinase kinase kinase (MAPKKK) that activates p38 MAPK pathways in oxidative stress-induced hepatotoxicity in D-galactosamine/lipopolysaccharide (D-GalN/LPS) model, is a key central pathway in which specific targeting of ASK1 deactivation is of a great therapeutic potential. We tested the effect of silibinin and vitamin E in curative and prophylactic manner of treatment on the negative modulators of ASK1, thioredoxin1 (Trx1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Numerous studies have shown that Trx1 plays an important role in ROS scavenging in various diseases through its protection against redox stress. [34][35][36][37][38] Moreover, the expression of Trx1 has been correlated with the activity of various Nox components, including Nox4, Nox2, p22 phox , and Rac. 39,40 Therefore, we presume that SelT may be a novel essential effector of the intracellular antioxidant system, which functions as Trx1, thus regulating Nox activity and ROS production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that Trx1 plays an important role in ROS scavenging in various diseases through its protection against redox stress. [34][35][36][37][38] Moreover, the expression of Trx1 has been correlated with the activity of various Nox components, including Nox4, Nox2, p22 phox , and Rac. 39,40 Therefore, we presume that SelT may be a novel essential effector of the intracellular antioxidant system, which functions as Trx1, thus regulating Nox activity and ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that SelT is a thioredoxin‐like enzyme, which has an active site (Cys‐Gly‐Pro‐Cys) similar to thioredoxin 1 (Trx1). Numerous studies have shown that Trx1 plays an important role in ROS scavenging in various diseases through its protection against redox stress 34‐38 . Moreover, the expression of Trx1 has been correlated with the activity of various Nox components, including Nox4, Nox2, p22 phox , and Rac 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…More intriguingly, apart from inflammatory responses, the excessive accumulation of reactive oxygen species (ROS) is recognized to a possible mechanism of d -GalN/LPS-induced FHF ( 9 ). ROS overproduction not only directly triggers oxidative damage but also activates the MAPK and NF-ÎșB signaling pathways, resulting in inflammatory responses that further stimulate inflammatory injury ( 10 , 11 ). Furthermore, nuclear factor erythroid 2-related factor 2 (Nrf2), which is a key transcription factor that is required to ameliorate various oxidative stress- and inflammation-associated diseases, regulates the expression of various antioxidant genes, including heme oxygenase-1 (HO-1), NAD (P) H: quinoneoxidoreductase 1 (NQO1), and the glutamate-cysteine ligase modifier (GCLM) and glutamate-cysteine ligase catalytic (GCLC) subunit ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced Trx1 could be a direct inhibitor or negative regulator of ASK1, while ROS stimulation could dissociate Trx1 from Trx1/ASK1 complex and lead to ASK1 activation and in turn result in the phosphorylation of its downstream substrate p38 MAPK [22, 26]. As mentioned above, we previously reported that contrast media exposure directly increased cellular oxidation and induced p38 AMPK/iNOS pathway mediated apoptosis in renal tubular cells in vitro and vivo [6, 7].…”
Section: Discussionmentioning
confidence: 99%